A study into the current state of Saiga tatarica L. populations with the use of retrospective data - Talgat Begilov; Yuriy Grachev; Birlikbay Eszhanov (Acta Scientiarum: Animal Sciences, 2024)
The saiga antelope (Saiga tatarica tatarica L., 1766, S) is a prominent ungulate mammal species inhabiting Central Asia. Over the latter half of the 20th century, saiga populations, including the Volga-Ural (Kazakhstan) population, experienced a continuous decline. However, there was a resurgence in their numbers in the 1980s. This study aims to assess the present status of saiga populations, particularly the Volga-Ural (V-U) population, by analyzing existing retrospective data. Our findings reveal that during the 21st century, the saiga population has increased in two key regions: the Volga-Ural and Betpak-Dala (B) populations. Notably, the Northern-Western Population (NWP) habitat saw a drastic 50-fold decline in population, while other populations decreased by 2.0-5.0 times. Despite this decline, the NWP habitat exhibited higher juvenile saiga yields compared to other regions. The resurgence of saiga populations has been significantly influenced by the support of the Government of Kazakhstan, along with the effective efforts of international wildlife conservation organizations and local community engagement.